Predictors of perceived stress and the mitigating role of physical activity among nurses employed in high-risk departments - Vuković, Vesna; Golubović, Vesna; Mihajlović, Milica; Jovanović, Dijana; Rodic, Branka (Education and Research in Health Sciences, 2026)
Introduction: Workplace stress represents a significant public health issue among healthcare professionals, particularly nurses employed in high-risk departments, where professional demands, responsibility, and exposure to stressors are pronounced. Aim of the paper: The aim of this study was to examine the relationship between perceived work-related stress, psychosomatic symptoms, behavioral and cognitive reactions to stress, perceived benefits of physical activity, and the level of perceived stress among nurses employed in high-risk work settings.Methods: The study was conducted as a cross-sectional design on a sample of 82 nurses employed in high-risk departments at the Clinical Center of Serbia and the Institute for Orthopedic Surgery “Banjica.” Perceived stress was assessed using the Perceived Stress Scale (PSS-10), while additional items examined work-related stress, psychosomatic symptoms, behavioral and cognitive reactions to stress, as well as the perceived effects of physical activity. Data were analyzed using descriptive statistics, Pearson correlation analysis, and multiple linear regression.Results: Work-related stress, psychosomatic symptoms, and behavioral and cognitive stress responses emerged as statistically significant predictors of perceived stress, with behavioral and cognitive responses showing the strongest contribution. Contrary to expectations, perceived benefits of physical activity were not significantly associated with perceived stress, although the direction of the association was negative.Conclusion: The obtained results indicate that perceived stress among nurses is significantly associated with work-related stressors, as well as with psychosomatic, behavioral, and cognitive reactions to stress. The findings highlight the need for a comprehensive approach to the prevention of occupational stress, including improvements in working conditions, strengthening of psychological support systems, and the promotion of healthy lifestyle habits, including regular physical activity.
Keywords: perceived stress; nurses; high-risk workplaces; physical activity; occupational stress; psychosomatic symptoms; behavioral and cognitive responses to stress